Pengaruh Kerjasama Sipil-Militer terhadap Pengelolaan Sistem Keamanan di Bandar Udara Internasional El Tari Kupang - Lilian Megawati; Kifni Yudianto (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Participation can remove mental barriers due to limited insight and limited viewpoints. Therefore, you are bound to discover your own assets and weaknesses, seek ways in which others can, adjust to respecting the receptive, and make beneficial arrangements. The safety of everyone in a room is associated with different security. This kind of exploration is a quantitative examination. The sample used in this population is 52 respondents. The information examination procedure used in this exploration is the Basic Straight Relapse Investigation and the use of the T test theory test. The results of this study indicate that participation does not have a significant effect on controlling the security framework, but various changes in the security framework can be made with joint military cooperation which is explained by the SPSS consequence of 0.157 or more than 0.05. The different results also show that the participation variable does not affect the security framework with SPSS results of 0.157 or more than 0.05. Keywords: Cooperation, Security